Corrosion resistance of layer-by-layer assembled polyvinylpyrrolidone/polyacrylic acid and amorphous silica films on AZ31 magnesium alloys. Issue 68 (1st July 2016) - Cui, Lan-Yue; Zeng, Rong-Chang; Li, Shuo-Qi; Zhang, Fen; Han, En-Hou
Abstract : A layer-by-layer (LbL)-assembled composite coating containing SiO2 and a biocompatible polyvinylpyrrolidone (PVP) and polyacrylic acid (PAA) multi-layer, designated as SiO2 /(PVP/PAA)5, was prepared on AZ31 Mg alloy via dip-coating. Abstract : A layer-by-layer (LbL)-assembled composite coating containing SiO2 and a biocompatible polyvinylpyrrolidone (PVP) and polyacrylic acid (PAA) multi-layer, designated as SiO2 /(PVP/PAA)5, was prepared on AZ31 Mg alloy via dip-coating. The surface morphology, microstructure and chemical composition of the coating were investigated using FE-SEM, FT-IR, XRD and XPS. The physical properties of the coating were characterized by scratch testing. The results demonstrated that the coating was amorphous and remarkably soft. PVP and PAA promoted the formation of Ca–P precipitates, and the amorphous silica film further enhanced corrosion resistance. The SiO2 /(PVP/PAA)5 coating may be a promising surface modification for degradable Mg cardiovascular stents.